The effect of Nigella sativa extract on mouse oocyte activation - Abdul Rahman, Suzanah; Enseri, Mohd Qairul Amir; Abdul Samat, Nadia Hanis (2014)
Female infertility cases have been increased worldwide by several factors including lifestyle. Nigella sativa is a well-known medicinal plant which has been used globally for prevention and cure of many diseases. Nigella sativa with its active components were thought to be a solution for the infertility problem. Thus in this experiment, the effects of Nigella sativa on the number of oocytes and number of fertilized oocytes were investigated. This was carried out by treating 20 Balb/c female mice divided equally into groups of four; i) control group (no treatment given), ii) treated with 25mg/kg per body weight of Nigella sativa, iii) treated with 50mg/kg per body weight of Nigella sativa, and iv) treated with 75mg/kg per body weight of Nigella sativa. The treatments were given daily for five days (estrous cycle) via intraperitoneal (i.p.) injection. Then, they were sacrificed and oocytes were obtained, followed by in vitro fertilization process. Total number of oocytes obtained was calculated and total number of fertilized oocytes was recorded. This study discovered that Nigella sativa supplementation did not indicate any significant difference (p>0.05) in the effect of different doses of Nigella sativa with total number of oocytes produced as well as the total number of fertilized oocytes. It was concluded that Nigella sativa did not increase the number of oocytes and the number of fertilized oocytes produced in mice.